AR-Assisted RME Model in Enhancing Mathematics Learning Outcomes and Literacy of Teacher Professional Education Students - Dahlan, Taufiqulloh; Hamdani, Acep Roni; Ginanjar Putra, Beni Yusepa (Jurnal Pendidikan MIPA, 2025)
The purpose of this study is to develop AR media based on Realistic Mathematics Education (RME) that is valid, practical, and effective in improving learning outcomes and literacy of Teacher Professional Education (TPE) students in basic mathematics lessons. The novelty of the study lies in the combination of AR media and the appropriate RME model at the TPE student level. The research method used the ADDIE development model. The number of respondents was 50 TPE students from Pasundan University, which divided into two classes. The mean scores for validity, as assessed by material experts, were 92.11%; learning model experts, 92.22%; media experts, 92.39%; and lecturers, 92.39%, with all categories demonstrating very high validity. For the mean practicality of student assessment of AR media and RME models, the mean was 92.01%, which falls into a very good category. A significant increase was observed in small group trials using AR Media based on the RME model, which has been proven effective, as evidenced by a 29.6-point increase from pre-test scores of 61.2 to post-test scores of 90.8. In large group trials, differences in learning outcomes were found between students who used AR media based on the RME model, with a mean of 90.8, and students who used other media based on the discussion model, with a mean of 69.5. The difference proved effective and very significant, with a mean difference of 21.3. Conclusion: Using RME-based AR media in mathematics learning for TPE students is more effective than using media with other learning models. The implication of this study is that TPE lecturers should encourage the implementation of AR media based on the RME model in the learning process.    Keywords: design, mathematical literacy, AR media, RME.